2006
DOI: 10.4049/jimmunol.177.6.4086
|View full text |Cite
|
Sign up to set email alerts
|

MaxiK Blockade Selectively Inhibits the Lipopolysaccharide-Induced IκB-α/NF-κB Signaling Pathway in Macrophages

Abstract: Macrophages have a pivotal function in innate immunity against bacterial infections. They are present in all body compartments and able to detect invading microorganisms with high sensitivity. LPS (endotoxin) of Gram-negative bacteria is among the most potent stimuli for macrophages and initiates a wide panel of cellular activation responses. The release of mediators such as TNF-α and ILs is essential for the initiation of a proinflammatory antibacterial response. Here, we show that blockade of the large-condu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
50
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(51 citation statements)
references
References 52 publications
1
50
0
Order By: Relevance
“…Papavlassopoulos et al demonstrated that LPS-induced NF-B activation in human and rat macrophages was inhibited by BK channel blockade and proposed that BK channels might participate in TNF-␣ production by controlling NF-〉-dependent gene transcription. 17 However, similar NF-B activation occurred in BK ϩ/ϩ and BK Ϫ/Ϫ BMDMs ( Figure 5D). Moreover, no differences in Akt and ERK phosphorylation were observed between BK ϩ/ϩ and BK Ϫ/Ϫ BMDMs, indicating that BK channels do not control TNF-␣ release or signal transduction pathways that are implicated in TNF-␣ generation and release in BMDMs.…”
Section: Resultsmentioning
confidence: 63%
See 3 more Smart Citations
“…Papavlassopoulos et al demonstrated that LPS-induced NF-B activation in human and rat macrophages was inhibited by BK channel blockade and proposed that BK channels might participate in TNF-␣ production by controlling NF-〉-dependent gene transcription. 17 However, similar NF-B activation occurred in BK ϩ/ϩ and BK Ϫ/Ϫ BMDMs ( Figure 5D). Moreover, no differences in Akt and ERK phosphorylation were observed between BK ϩ/ϩ and BK Ϫ/Ϫ BMDMs, indicating that BK channels do not control TNF-␣ release or signal transduction pathways that are implicated in TNF-␣ generation and release in BMDMs.…”
Section: Resultsmentioning
confidence: 63%
“…17 Using the BK channel inhibitors IbTX and paxilline, we observed that the dose-dependent LPS-induced TNF-␣ production in For personal use only. on May 11, 2018.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…31 PGN is also a ligand of TLR2, suggesting that TLR2 or TLR4 might change intracellular K þ levels. Interestingly, TLRs and IL-1R were recently shown to associate and functionally depend on the large-conductance Ca 2 þ -activated K þ channel MaxiK 32,33 Since this K þ channel is abundantly expressed in macrophages, we could speculate that the activators MSU, PGN and probably imidazoquinoline activate the inflammasome via a MaxiK-mediated K þ efflux. However, the use of MaxiK inhibitor paxilline did not inhibit caspase-1 activation (data not shown), suggesting that different K þ channelforming proteins are involved.…”
Section: Discussionmentioning
confidence: 99%